Designing mobile learning: Empirical journey to reality in Malaysian secondary school context - Rashidah Rahamat (EduLite: Journal of English Education, Literature and Culture, 2019)
Designing a conducive and meaningful learning environment in the teaching and learning is thought-provoking tasks. The use of teaching materials will be one of the resources and normally teachers or the practitioners will need to put a lot of considerations will assist teachers in creating the desired learning outcomes. This paper aims to share the initial steps engaged in the process of creating a mobile learning concept which is applicable for Malaysian Secondary School Education. Therefore, the mixture of qualitative and quantitative measure was deployed in order to achieve the primary objective of creating a workable mobile learning concept. The findings from analysing 40 documents had unlocked a few gaps to be filled in: they enabled the focus to be on the small “l” component for the English Language secondary school syllabus as well as on the feasible methodology to be applied for the real mobile language learning context. Whereas the input from the need analysis provided more insights on how the content for the dry literature components could be arranged in the learning context. Hence, by combining the input from the documents analysis and need analysis data, they had proven to be empirically and beneficially useful steps to be taken before embarking on the actual conception of any teaching and learning design to be proposed or implemented. These initial steps had proven to be beneficial for the next stage of designing the mobile learning environment in Malaysian secondary school context.